“Estudio del sistema integral de agua potable, alcantarillado sanitario y pluvial en la lotización las peñitas i, perteneciente al cantón Arenillas provincia de el Oro” - Palacios Bahamonde, Katherine Pamela (2015)
The Municipality of the Canton Arenillas , noting that currently the Allotment does not have the basic services to which every citizen is entitled is investing in the construction of potable water, sanitary sewer and storm sewer . This leads to the justification for performing the different studies and designs networks in the Allotment Las Peñitas . This project will solve various problems that arise in the population, such as formation of pools of water that generate health problems , as well as the use of septic tanks that are sewage collectors .